Levels of Aureomycin and the comparative value of dehydrated alfalfa and Elodea canadensis meals in swine-fattening rations. - Richardson, D. (Kansas Agricultural Experiment Station, 2011)
The amount of antibiotic generally recommended in swine-fattening rations is 5 mg. per pound of total feed consumed. Some workers have felt that higher levels might produce more rapid and economical gains. One purpose of this test was to compare results with 5 and 20 mg. of aureomycin per pound of complete feed Elodea canadensis is a plant which grows in fresh-water lakes and ponds. Upon dehydration and grinding, it looks about the same as dehydrated alfalfa meal. The second purpose of this experiment was to compare the value of dehydrated alfalfa and Elodea canadensis meals in swine-fattening rations. Table 30 gives the chemical analysis of the Elodea canadensis meal used. Sixteen weanling pigs were divided as equally as possible into lots of four pigs each on the basis of weight, sex, and breed. The pigs were fed a complete ration, shown in Table 31. It contained about 18 percent protein and was fed till the pigs reached approximately 75 pounds body weight. The protein level of the ration was 15 percent from 75 to approximately 125 pounds body weight. It was then lowered to 12 percent protein for the remainder of the experiment. Adjustments in protein were made by adding corn and removing part of the tankage and soybean meal. Aureomycin was added in the form of Aurofac 2A. Elodea canadensis was substituted for equal amounts of alfalfa meal. Water was available at all times.
Keywords: Swine; Aureomycin; Alfalfa Elodea canadensis; Dehydrated alfalfa